New insights into the lifestyle of Allosaurus (Dinosauria: Theropoda) based on another specimen with multiple pathologies - Christian Foth; Serjoscha W. Evers; Ben Pabst; Octávio Mateus; Alexander Flisch; Mike Patthey; Oliver W.M. Rauhut (PeerJ, 2015)
Adult large-bodied theropods are often found with numerous pathologies. A large, almost complete, probably adult Allosaurus specimen from the Howe Stephens Quarry, Morrison Formation (Late Kimmeridgian–Early Tithonian), Wyoming, exhibits multiple pathologies. Pathologic bones include the left dentary, two cervical vertebrae, one cervical and several dorsal ribs, the left scapula, the left humerus, the right ischium, and two left pedal phalanges. These pathologies can be classified as follows: the fifth cervical vertebra, the scapula, several ribs and the ischium are probably traumatic, and a callus on the shaft of the left pedal phalanx II-2 is probably traumatic-infectious. Traumatically fractured elements exposed to frequent movement (e.g., the scapula and the ribs) show a tendency to develop pseudarthroses instead of a callus. The pathologies in the lower jaw and a reduced extensor tubercle of the left pedal phalanx II-2 are most likely traumatic or developmental in origin. The pathologies on the fourth cervical are most likely developmental in origin or idiopathic, that on the left humerus could be traumatic, developmental, infectious or idiopathic, whereas the left pedal phalanx IV-1 is classified as idiopathic. With exception of the ischium, all as traumatic/traumatic-infectious classified pathologic elements show unambiguous evidences of healing, indicating that the respective pathologies did not cause the death of this individual. Alignment of the scapula and rib pathologies from the left side suggests that all may have been caused by a single traumatic event. The ischial fracture may have been fatal. The occurrence of multiple lesions interpreted as traumatic pathologies again underlines that large-bodied theropods experienced frequent injuries during life, indicating an active predatory lifestyle, and their survival perhaps supports a gregarious behavior for Allosaurus. Alternatively, the frequent survival of traumatic events could be also related to the presence of non-endothermic metabolic rates that allow survival based on sporadic food consumption or scavenging behavior. Signs of pathologies consistent with infections are scarce and locally restricted, indicating a successful prevention of the spread of pathogens, as it is the case in extant reptiles (including birds).